2014
DOI: 10.1007/s11745-014-3914-7
|View full text |Cite
|
Sign up to set email alerts
|

Fish Oil Supplementation Decreases Oxidative Stress but Does Not Affect Platelet‐Activating Factor Bioactivity in Lungs of Asthmatic Rats

Abstract: Dietary fish oil supplementation increases the content of n-3 polyunsaturated fatty acids (PUFA) in cellular membranes. The highly unsaturated nature of n-3 PUFA could result in an enhanced lipid peroxidation in the oxidative environment characteristic of asthma. The oxidative reaction cascade culminates in an increased production of components associated to oxidative stress and of an important proinflammatory mediator platelet-activating factor (PAF)-like lipid. We evaluated the effect of fish oil supplementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…Fish oil supplementation significantly lowered the concentrations of both BALF nitrite (~30%, p < 0.005) and lipid hydroperoxide (~40%, p < 0.001) in asthmatic rats. 15 Furthermore, increased antioxidant levels of superoxide dismutase (~40%, p < 0.05) and glutathione peroxidase (13-fold increase, p < 0.05) were observed in the fish-oil asthma group as compared to the control group. 15 Fish oil also resulted in significantly lower catalase activity (p < 0.001) in non-asthmatic rats.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Fish oil supplementation significantly lowered the concentrations of both BALF nitrite (~30%, p < 0.005) and lipid hydroperoxide (~40%, p < 0.001) in asthmatic rats. 15 Furthermore, increased antioxidant levels of superoxide dismutase (~40%, p < 0.05) and glutathione peroxidase (13-fold increase, p < 0.05) were observed in the fish-oil asthma group as compared to the control group. 15 Fish oil also resulted in significantly lower catalase activity (p < 0.001) in non-asthmatic rats.…”
Section: Resultsmentioning
confidence: 90%
“…15 Furthermore, increased antioxidant levels of superoxide dismutase (~40%, p < 0.05) and glutathione peroxidase (13-fold increase, p < 0.05) were observed in the fish-oil asthma group as compared to the control group. 15 Fish oil also resulted in significantly lower catalase activity (p < 0.001) in non-asthmatic rats. 15 …”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…However, there was no effect on the bioactivity of a pro-inflammatory mediator (platelet-activating factor) in lung tissue (38). Further suggesting complex and divergent effects of the components of fish oil supplements on allergic airway inflammation, an experiment in OVA-sensitized mice showed that high dietary intake of DHA for 6 weeks leads to significantly increased eosinophils and IL-6 in BAL, and a trend for increased levels of IL-4 and IL-13 in BAL.…”
Section: Introductionmentioning
confidence: 99%